Highlighting the role of traditional paddy for sustainable agriculture and livelihood: issues, policy intervention and the pathways - Patra, Sabyasachi; Saha, Ayan; Pal, Subodh Chandra; Islam, Abu Reza Md. Towfiqul; Halder, Krishnagopal; Srivastava, Amit Kumar; Pande, Chaitanya Baliram; Islam, Aznarul; Costache, Romulus; Alam, Edris; Islam, Md. Kamrul (Discover sustainability, 2025)
Traditional paddy cultivars (TPC) have a high nutritional and medicinal value and can survive severe stress conditions. TPCs are soil and region-specific, produced with organic manure, and free of pesticides or insecticides; as a result, they are more resistant to pests and naturally strong. TPCs are the best solution to the issues of unpredictable rainfall and aid in preventing pest infection since climate change does not affect them, such as increases or decreases in temperatures, humidity, and drought. TPCs are more valuable on the market than new high-yielding and improved varieties and need less labour to grow. Traditional rice has been used to treat various specific conditions, including high blood pressure, digestive system issues, skin inflammation, and blood sugar regulation. This review aims to educate farmers, seed growers, and researchers receiving valuable information regarding the importance of different TPC and cultivating more areas of suitable traditional cultivars of paddy for sustainable agriculture. Therefore, it is crucial to put policies in place to properly preserve farmers' variety if agriculture is to thrive sustainably.